A low-light radiative transfer model for satellite observations of moonlight and earth surface light at night. (May 2020) - Min, Min; Zheng, Jianyu; Zhang, Peng; Hu, Xiuqing; Chen, Lin; Li, Xi; Huang, Yu; Zhu, Lin
Highlights: New Low-Light Radiative Transfer Model with active surface light sources is developed. The simulation of the new model has a minimal bias compared with the DISORT model. The new model shows potential to simulate space-based low-light imager observations. Abstract: Lunar sun-reflected light can be effectively measured through a low-light band or a day/night band (DNB) implemented on space-based optical sensors. Based on moonlight, nocturnal observations for artificial light sources at night can be achieved. However, to date, an open-sourced and mature Low-Light Radiative Transfer Model (LLRTM) for the further understanding of the radiative transfer problem at night is still unavailable. Therefore, this study develops a new LLRTM at night with the correction of the lunar and active surface light sources. First, the radiative transfer equations with an active surface light source are derived for the calculation based on the lunar spectral irradiance (LSI) model. The simulation from this new LLRTM shows a minimal bias when compared with the discrete ordinates radiative transfer (DISORT) model. The simulated results of radiance and reflectance at the top of the atmosphere (TOA) also show that the surface light source has a remarkable impact on the radiative transfer process. In contrast, the change in the lunar phase angle has minimal influence. Also, comparing with space-based DNB radiance observations, LLRTM shows the potential to simulate space-based low-light imager observations under an effective surface light source condition during the night.